Coverage‐Limiting Factors Affecting the Monitoring of Urban Emissions With the Orbiting Carbon Observatory Missions - Dustin Roten; Abhishek Chatterjee (AGU Advances, 2025)
Abstract A growing number of space‐based platforms, like the Orbiting Carbon Observatory (OCO‐2 and OCO‐3) missions, observe Earth's atmospheric carbon dioxide CO2 concentrations with high accuracy and precision. With the original goal of constraining natural CO2 fluxes at regional to global scales, these instruments have now become popular tools for studying anthropogenic emissions from cities around the world. As signatories of the Paris Climate Agreement are expected to produce nationally determined contributions (NDC) to global carbon emissions, continued monitoring, reporting, and verification (MRV) of these estimates will be essential. While the use of OCO‐2 and OCO‐3 missions for MRV purposes is increasing, several physical and environmental factors limit data collection. Using the continental United States as a test case, the influences of orbital mechanics and environmental factors on local‐ and national‐level emissions estimates are explored through a series of linear and multi‐linear regressions to predict each instrument's effective revisit time. Results suggest that, due to environmental factors, western regions of the U.S. are more likely to be constrained at a sub‐annual scale than eastern regions, with effective instrument revisit times <30 days. East coast cities have effective revisit times >30 days; however, this varies seasonally. The characteristics of the instruments' orbits also vary the frequency of urban observations in both space and time. Implications for observation‐derived emission estimates at local and national scales and remedies for such shortcomings in future missions are discussed.